603 VTE Prophylaxis Compliance on The Burns Unit. (12th October 2021) - Sayed, M A; Murray, E; Soueid, A
Abstract: Aim: To assess if VTE risk assessments are correctly completed and implemented on the Burns Unit. Method: 2-week prospective analysis of all inpatients admitted to the adult Burns Unit. Data was collected from patient files and drug Kardexs. Variables including TBSA, date of injury, date of admission, date of VTE risk assessment score, correct prescription according to score and implementation were compiled in an excel spread sheet. Audited against Trust and NICE Guideline 89. Results: The first cycle identified errors in risk assessment completion related to inaccurate BMI assessment and failure to identify the burn as a risk factor. The risk assessment was only re-assessed 71% of the time post operatively or following change in condition. An action plan included re-education of medical staff, reminder posters in theatre and re-designing the burns operation note to include a VTE re-assessment tick box. A re-audit showed an improvement in correct VTE scoring from 65% to 100% and VTE reassessment from 71% to 100%. Conclusions: Following the first cycle, Wythenshawe Hospital Burns Unit has improved in compliance with the NICE and Trust Guidelines. The two most frequent errors identified on completion of the risk assessment form have not been seen in the second cycle following education of medical staff. All patients should continue to be prescribed the prophylaxis indicated, unless contraindicated. For those patients who cannot wear AES due to a burn to their lower legs, flowtrons and/or enoxaparin should be considered instead. For those patients who refuse treatment an incident form must be completed.